Distribution chart of Holocene benthic foraminifera in the Izu-Bonin Arc (Table 2) - Kunio Kaiho; Akira Nishimura (PANGAEA, 1992)
The distribution of Holocene benthic foraminifer species in bottom sediments in the Izu-Bonin Arc region of the northwestern Pacific Ocean has been investigated on the basis of 23 samples recovered from depths between 1100 and 4100 m. The benthic foraminifer faunas identified can be grouped into four species assemblages corresponding to four bathymetric zones: the abyssal zone (below 3700 m water depth), lower bathyal zone (2600-3600 m), lower middle bathyal zone (1600-2300 m), and upper middle bathyal zone (above 1300 m). The dominance of such an agglutinated foraminifer as Rhabdamminella sp. characterizes the abyssal zone, whereas assemblages devoid of calcareous foraminifers distinguish the zone deeper than the carbonate compensation depth (CCD). The occurrence of Bulimina aculeata d extquotesingleOrbigny enables the recognition of the following three bathymetric zones: the lower bathyal zone characterized by such deep-sea species as Oculosiphon sp., Saccorhiza ramosa (Brady), Alabamina sp., and Pullenia bulloides (d extquotesingleOrbigny); the lower middle bathyal zone defined by the occurrence of B. aculeata; and the upper middle bathyal zone characterized by the lack of B. aculeata as well as the dominance of such species as Uvigerina proboscidea Schwager and Sphaeroidina bulloides d extquotesingleOrbigny. To estimate Quaternary and Pliocene paleobathymetry in the Izu-Bonin region, three water-depth indexes will work well: 3700 m for the CCD, 2300 m for the deepest habitat of B. aculeata, and 1600 m for the shallowest habitat of B. aculeata.
Supplement to: Kaiho, K; Nishimura, A (1992): Distribution of Holocene benthic foraminifers in the Izu-Bonin Arc. In: Taylor, B; Fujioka, K.; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 126, 311-320, https://doi.org/10.2973/odp.proc.sr.126.138.1992